Bacillus thuringiensis development from 1971 to 1996: Cases of a research group in Brazil - Moraes, I. O.; Capalbo, D. M. F.; Arruda, R. O. M.; Bianchi, Vanildo Luiz Del [UNESP] (My University, 1998)
Brazil is internationally known for its activities in mass production and use of biocontrol agents. Batch studies on Bacillus thuringiensis fermentation were initiated in 1970, at the State University of Campinas (UNICAMP) to explore the feasibility of producing endotoxin preparations, using cheap liquid by-products as fermentation substrates. The culture media composition, its price, and their influence on the final cost were studied for mini- and pilot-scale production. The results obtained generated two industrial patents on the fermentation process, using sugar cane molasses and corn steep liquor as sources of nutrients. Besides these studies, others such as rheological characteristics of many culture media and the culture broths, the influence of aeration and agitation levels on growth and sporulation, the continuous technique affecting growth and sporulation rate, the effects of different ways of drying on the viability of the spores and the potency of the insecticide obtained, as well as the solid state fermentation were developed. These studies were done as Master and Ph.D. theses, and some results were published from 1971 to 1996.
Keywords: Agroindustrial residues; Bacillus thuringiensis case studies; Biopesticide; Endotoxin preparations; Fermentation processes; Low cost substrates; Waste water residues